THE STANDARD OF COMMUNITY BASED TOURISM MARKETING: A CASE STUDY OF KLONGDAEN COMMUNITY, THAILAND - Khlaikaew, Kunkaew; Buakwan, Narawadee; Chaiyakot, Pratchayakorn (PEOPLE: International Journal of Social Sciences, 2017)
Community-based tourism has been identified as a sustainable alternative to mainstream tourism for not only big cities but also small communities throughout Thailand. Klongdaen community of Songkra Province in southern Thailand is not an exception. The community relies largely on tourism revenues, yet marketing research has not been a focal point of study. This study; therefore, attempts to (1) verify tourism products and services; and (2) identify the patterns of marketing relevant to the context of the community. Field survey, observation, focus group discussion, and in-depth interview were used to collect data.The results showed that the prevalent tourism products and services consist of natural sites, cultural sites, religious sites, community history, local legends and anecdotes, local wisdoms, local arts and performances, local handicrafts, local foods, local festivals, tourism activities, homestay services, and other tourism services. In addition to this, four patterns of community-based tourism marketing namely; manufacturing local products and services; fair pricing; sustainable marketing channel; and responsible sales promotion were also found.